Environmental Assessment of Methane (CH4) Emissions From Different Land Management Systems. A Case of the Central Chernozem State Biosphere Nature Reserve Named After Professor V.V. Alyokhin - Tembo, Allan; Musenge, Danny Chisanga; Muyabe, Otton; Mhango, Jestone (Food, Agriculture and Natural Resources - NETWORKS, 2025)
This study investigates methane (CH4) emissions from various land management systems in the Central Chernozem State Biosphere Nature Reserve of the Russian Federation. Land management systems considered in this study include: Non-Mowed Virgin Steppe (NMVS), Forest Ecosystem (FE), Meadow Land Ecosystem (MLE), Clean Fallow Ecosystem (CFE), 5-Year Rotational Mowed Steppe (5RMS), and 10-Year Rotational Mowed Steppe (10RMS). Using the static-closed gas chamber method, and gas chromatography, the study reveals that FE, NMVS, 5RMS and 10RMS acted as CH4 sinks with negative fluxes, indicating CH4 oxidation surpassing production. MLE and CFE exhibit positive CH4 emissions, considerably attributed to anaerobic conditions favouring methanogenesis due to soil disturbance. Soil temperature shows moderate positive correlation (0.6) with CH4 emissions, demonstrating temperature sensitivity of methanogenic microbial activity. Soil moisture displays a weaker correlation (0.2), but remains significant in influencing CH4 dynamics. The study recommends promoting Non-Mowed and Rotational Mowed Steppes for their CH4 sink potential, and implementing soil aeration strategies in MLE and CFE ecosystems to mitigate emissions. Continuous monitoring and adaptive management are essential for optimizing land management to reduce greenhouse gas emissions. This research provides a foundation for developing effective CH4 mitigation strategies, contributing to broader climate change mitigation efforts.